Futsal Field Selection Application Using Mobile-GIS and GPS with Dijkstra's Algorithm Method (Lhokseumawe City Case Study) - Rahmat Triandi; Asrianda; Lidya Rosnita (ARRUS Journal of Engineering and Technology, 2022)
Futsal field rental is a business engaged in the field of community service in the field of futsal sports. Currently in lhokseumawe city there are 10 futsal fields located in various places, ranging from around campus, office areas, to densely populated settlements. This resulted in many of the people who do not know the location of the futsal field and also the nearest route that can be passed. So it takes an application that can provide information on the futsal field in lhokseumawe city along with the nearest route that can be passed. Determining the nearest route passed to the location of the futsal field can only be done on nodes that have been defined by the system. Dijkstra's algorithm was chosen because it operates thoroughly against existing nodes, and generates the shortest trajectory of all nodes so that it will produce the nearest route optimally. To test the accuracy of the nearest route the results of dijkstra algorithm implementation are used another software that is quantum GIS. This is done to see if the resulting path is correct. From the test results obtained the path obtained is the same as quantum GIS calculations with a similarity value of 100%. Black box testing is used to test the functionality of the menus in the system, and the test results in terms of the functionality of the menus on the system run as desired and run well. The system is good to use.